Profil Kemampuan Literasi Sains Peserta Didik Berdasarkan Instrumen Scientific Literacy Assessments (SLA) - Rohana Rohana; Asrial Asrial; Zurweni Zurweni (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2020)
This study aims to describe the profile of science literacy ability of MTs learners in Jambi city based on Scientific Literacy Assessments (SLA) instruments. The research method used is quantitative method with descriptive research type. The subjects in this study were students of MTs Negeri 2 Jambi city and MTs Laboratory UIN STS Jambi City. The study sampled 98 students. Based on the results of the study, the average achievement of science literacy ability of learners in the low category with a score of 50.01. Of the five aspects of science literacy, only one aspect is in the high theories, namely science motivation and beliefs with a score of 75.53, three aspects are in the low category, namely role of science with a score of 50.26, science and society with a score of 51.17 and mathematics in science with a score of 50.34 while the scientific thinking and doing aspect is in the very low category with a score of 27.78. In conclusion, the average literacy achievement of MTs learners with scientific literacy assessments (SLA) instruments in the low category. Keywords: Ability, Science Literacy, Scientific Literacy Assessments (SLA)